Phytochemical assay, potential of antimalarial and antioxidant activities of green tea extract and its fraction - Fanny Rahardja (Biomedical Engineering, 2015)
Objective : The research objective was to evaluate the phytochemical compounds, the antioxidant and anti-malarial activity of green tea extract and its fraction. Methods : The antioxidant activity were measured by 1,1-diphenyl-2-picryl-hydrazyl (DPPH) scavenging activity used in vitro laboratories prospective experimental design and completely randomized design, using ethanol extract, hexane, ethyl acetate, butanol fraction, and water fraction of green tea in 7 levels of concentration compared to epicatechin (EC). The data were analyzed using linear regression analysis, and were continued by determined Inhibitory Concentration50 (IC50). The anti-malarial activity of green tea fractions were compared to artemisinin. The data were analyzed using probit analysis, and were continued by determined IC50 .Result: The results showed that the highest antioxidant activity (IC50) was the fraction of ethyl acetate 2,184 µg/ml. The anti-malarial activity IC50of water and ethyl acetate fraction, ethanol extract and butanol fraction were 0,000090 µg/mL,0,003 µg/mL, 0,006 µg/mL, 0,011 µg/ml respectively.Conclusion : Extract and fractions of green tea have potential anti-malarial and antioxidant properties.